Mengubah Paradigm: Edukasi Masyarakat tentang Pentingnya Pendidikan Lanjut Bagi Generasi Muda Melalui Layanan Informasi di Desa Sugaring Bayu Kecamatan Bandar Kabupaten Simalungun - Firda Aulia Mawaddah; Sakira Al Anikmah; Radna Keumala Rangkuti; Indah Nurhalizah (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to understand the role of information services in educating the community of Sugarang Bayu Village, Bandar Sub-district, Simalungun Regency, about the importance of further education for the younger generation. The research used a field method with a descriptive qualitative approach. Data was obtained through direct observation and in-depth interviews with three main informants: Sugarang Bayu Village Head, Pema Uinsu Chairperson, and Pema Uinsu Head of Activities. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results showed that the low interest of young people in the village to continue their education to higher education is influenced by four main factors: economic limitations, distance and accessibility, lack of support and motivation, and the deep-rooted culture of marrying young. The findings also revealed that information services have an important role in changing the community paradigm through effective information dissemination, education and delivery of educational opportunities. In conclusion, appropriate information services can increase community awareness about the importance of further education and help young people in Sugarang Bayu village to be more confident in achieving a better future through higher education.